Japanese encephalitis virus invasion of cell: allies and alleys. (23rd December 2015) - Nain, Minu; Abdin, Malik Z.; Kalia, Manjula; Vrati, Sudhanshu
Summary: The mosquito‐borne flavivirus, Japanese encephalitis virus (JEV), is the leading cause of virus‐induced encephalitis globally and a major public health concern of several countries in Southeast Asia, with the potential to become a global pathogen. The virus is neurotropic, and the disease ranges from mild fever to severe hemorrhagic and encephalitic manifestations and death. The early steps of the virus life cycle, binding, and entry into the cell are crucial determinants of infection and are potential targets for the development of antiviral therapies. JEV can infect multiple cell types; however, the key receptor molecule(s) still remains elusive. JEV also has the capacity to utilize multiple endocytic pathways for entry into cells of different lineages. This review not only gives a comprehensive update on what is known about the virus attachment and receptor system (allies) and the endocytic pathways (alleys) exploited by the virus to gain entry into the cell and establish infection but also discusses crucial unresolved issues. We also highlight common themes and key differences between JEV and other flaviviruses in these contexts. Copyright © 2015 John Wiley & Sons, Ltd.